Ethnomathematical Insights into Student Errors: Javanese Calendar and Pigeonhole Principle - Ahmad Ryan Hidayat; Ali Shodikin; Salma Hasna Hamiydah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This article aims to examine the implications for student learning by investigating student errors through the lens of the pigeonhole principle and the Javanese calendar. Method: The study used a descriptive qualitative research method and included six high school students and vocational students. Data collection involved tests and interviews. The researchers focused on Ethnomathematics problems related to the Javanese calendar system. Result: The analysis of student responses revealed several types of errors based on Watson's criteria for error analysis in problem-solving. These errors included inappropriate data, inappropriate procedure, and undirected manipulation. Students struggled with understanding the given information, selecting appropriate procedures, and applying logical reasoning. Novelty: Interestingly, the researchers found that when the students were provided with guidance and assistance, they were able to grasp the concepts and successfully solve the problems. This suggests that the students had the potential to understand the material but lacked prior exposure to the concepts, particularly the pigeonhole principle.